2020
DOI: 10.1002/humu.24033
|View full text |Cite
|
Sign up to set email alerts
|

Clinical validity of expanded carrier screening: Evaluating the gene‐disease relationship in more than 200 conditions

Abstract: Clinical guidelines consider expanded carrier screening (ECS) to be an acceptable method of carrier screening. However, broader guideline support and payer adoption require evidence for associations between the genes on ECS panels and the conditions for which they aim to identify carriers. We applied a standardized framework for evaluation of gene‐disease association to assess the clinical validity of conditions screened by ECS panels. The Clinical Genome Resource (ClinGen) gene curation framework was used to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…Ben‐Shachar et al and Guo and Gregg concluded that a panel meeting the “carrier frequency of 1 in 100 or greater” criterion would include approximately 40 conditions when that threshold is applied to any ethnicity 19,22 . Balzotti et al examined the “well‐defined phenotype” criterion by applying the ClinGen framework for gene‐disease association evidence 23 to more than 200 genes commonly included on commercial ECS panels, and found that the vast majority had the highest level gene‐disease association evidence 24 . These studies, taken together with ours, provide evidence‐based interpretations of ACOG panel design criteria and act as guidance for laboratories in the design of ECS offerings.…”
Section: Discussionmentioning
confidence: 99%
“…Ben‐Shachar et al and Guo and Gregg concluded that a panel meeting the “carrier frequency of 1 in 100 or greater” criterion would include approximately 40 conditions when that threshold is applied to any ethnicity 19,22 . Balzotti et al examined the “well‐defined phenotype” criterion by applying the ClinGen framework for gene‐disease association evidence 23 to more than 200 genes commonly included on commercial ECS panels, and found that the vast majority had the highest level gene‐disease association evidence 24 . These studies, taken together with ours, provide evidence‐based interpretations of ACOG panel design criteria and act as guidance for laboratories in the design of ECS offerings.…”
Section: Discussionmentioning
confidence: 99%
“…8 We therefore used ACMG's recommended quantification and threshold for evaluating genotype-phenotype relationship. Of the 176 conditions examined here, 175 (99.4%) met the moderate or higher gene-disease association threshold 22 (Figure 1B). This 175-condition panel would capture 99.8% of carriers and >99.9% of ARCs compared with a 176-condition panel (Supplemental Table 6).…”
Section: Genotype-phenotype Relationship As a Criterion For Panel Inclusionmentioning
confidence: 92%
“…Criterion 1 was defined by carrier frequency thresholds described in ACOG and ACMG criteria and evaluated using carrier rates from 460,608 individuals across 11 races/ethnicities (as seen further on). Criterion 2 was defined as gene-disease association and evaluated by applying the ClinGen clinical validity framework, which quantifies gene-disease association by assessing the strength of available evidence, 22 as recommended by ACMG. Criteria 3 to 5 were defined as factors of severity and were evaluated by mapping criteria to disease traits reported in Arjunan et al 23 Criterion 6 was evaluated using published age of onset data (Supplemental Table 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This framework has been applied to many monogenic conditions, including those commonly included on ECS panels, with classifications published on the ClinGen website. [43][44][45][46][47][48] This provides a valuable resource for considering which conditions are appropriate for inclusion on ECS panels.…”
Section: Genotype-phenotype Associationmentioning
confidence: 99%